Optimization of Islamic Financial Schemes for MSMEs Development - Nasrulloh, Agus Ahmad; Nurhasanah, Elis; Sukmawati, Heni; Joni, Joni (EKONOMIKA SYARIAH : Journal of Economic Studies, 2024)
Abstract The growth rate of Micro, Small, and Medium Enterprises (MSMEs) in the City/District of Tasikmalaya has increased steadily over the past six years at around 6.18% annually. MSMEs face challenges related to capital and business development, and the proposed solution is cooperation with financial institutions. However, MSMEs find it difficult to obtain financing from formal financial institutions due to a lack of collateral and sufficient knowledge about financing schemes suitable for their businesses. As a result, MSMEs have to seek funding from non-formal lenders with ribawi contracts, which contradict Islamic principles and local regulations. This practice is also inconsistent with Local Regulation No. 7 of 2014 of Tasikmalaya City and Governor Regulation No. 1 of 2022 of West Java. The aim of this research is to analyze opportunities, challenges, and strategies for optimizing shariah finance in the MSME sector in Tasikmalaya City/Regency. The type of research carried out was descriptive research with a mixed-method approach (qualitative and quantitative) using the Analytic Network Process (ANP). There were 8 respondents in this research, consisting of academics, practitioners, and regulators of Islamic financial institutions in Tasikmalaya City/Regency. The research results show that there are four problems and four solutions to optimize Islamic financial schemes in developing MSMEs, namely community problems, institutions, access, and regulations. The problems and solutions that must be addressed are primarily in society. Massive Islamic financial education needs to continue to be carried out, supported by access to Islamic financing and also the government's firmness in supporting MSMEs through Islamic financial institutions. Tingkat pertumbuhan UMKM di Kota/Kabupaten Tasikmalaya meningkat stabil selama enam tahun terakhir dengan pertumbuhan 6,18% setiap tahunnya. UMKM mengalami kendala terkait modal dan pengembangan usaha, dan solusi yang diusulkan adalah kerjasama dengan lembaga keuangan. Namun, UMKM kesulitan mendapatkan pembiayaan dari lembaga keuangan resmi karena tidak memiliki jaminan dan pengetahuan yang cukup tentang skema pembiayaan yang cocok untuk bisnis mereka. Akibatnya, UMKM harus mencari dana dari pemberi pinjaman non-formal dengan akad ribawi, yang bertentangan dengan prinsip Islam dan regulasi setempat. Praktik ini juga tidak sejalan dengan Peraturan Daerah Kota Tasikmalaya Nomor 7 Tahun 2014 dan Peraturan Gubernur Jawa Barat Nomor 1 Tahun 2022. Tujuan dari penelitian ini adalah untuk menganalisis peluang, tantangan dan strategi optimalisasi keuangan syariah pada sektor UMKM di Kota/Kabupaten Tasikmalaya. Jenis penelitian yang dilakukan adalah penelitian deskriptif dengan pendekatan Mixed Method (kualitatif dan kuantitatif) dengan menggunakan Analytic Network Process (ANP). Terdapat 8 orang responden dalam penelitian ini yang terdiri dari praktisi, akademisi, dan regulator lembaga keuangan syariah di Kota/Kabupaten Tasikmalaya. Hasil penelitian menunjukkan bahwa terdapat empat permasalahan dan empat solusi untuk mengoptimalkan skema keuangan syariah dalam mengembangkan UMKM, yaitu permasalahan masyarakat, kelembagaan, akses, regulasi. Permasalahan dan solusi yang harus dibenahi terutama pada masyarakat. Edukasi keuangan syariah secara masif perlu terus dilakukan, didukung dengan akses pembiayaan syariah dan juga ketegasan pemerintah dalam mendukung UMKM melalui lembaga keuangan syariah.